PENGEMBANGAN USAHA KELOMPOK PETERNAK ITIK - Dyah Lestari Yulianti; Siti Halimatus Sakdiyah (Publisher UPT P2M Politeknik Negeri Malang, 2016)
Community service groups duck breeders in the village Wonokerso districts Pakisaji aims to improve the knowledge and skills of farmers in the utilization and processing of potential sources of local feed ingredients, exploitation of breeding stock is superior, then is able and skilled in processing of livestock products as well as the processing of manure waste into organic fertilizer, so as to increase the income and welfare of farmers. IbM program results indicate that the public response duck farmers are very good and enthusiastic for proactive follow the program in all the activities for outreach, training, demoplot, mentoring and evaluation. The existence of these service programs have a positive impact on the environment ie partners provide solutions or alternative solutions to problems faced by groups of farmers in the village and the surrounding community. In the early stages of coordination of activities with the partner group leaders assisted with student involvement. Submission of this extension materials with discussions to evaluate the response of farmers to the material activities and sharing of experiences between the teams servant with targeted partners. The benefits of these activities can increase motivation and attention of farmers to practice the material in accordance with the activities of the problems faced, so that at the end of this activity can be a solution to the problems or difficulties faced by farmers in the field. The visit was also carried out at the end of the activity to evaluate how far the understanding group of farmers against the material provided. Groups of farmers and communities want their sustainable activities, not just stop at the end of this activity alone. Food products, agro-processing and organic fertilizers as well as the birth of calves that excel not just a dream but a reality that they or ranchers are able and can market the results or the products they make. Thus the community service program activities can be an opportunity for them to improve the income and welfare of his life.